2015
DOI: 10.1194/jlr.m052746
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue takes up plasma triglycerides mostly after lipolysis

Abstract: Brown adipose tissue (BAT) is an important player in energy homeostasis due to its ability to combust energy toward heat by virtue of the presence of uncoupling protein 1 (UCP1), a process called nonshivering thermogenesis ( 1 ). The most well-known trigger for activation of BAT is cold, which increases sympathetic outfl ow from the hypothalamic temperature center toward BAT. Here, nerve endings release noradrenalin that binds to adrenergic receptors on the brown adipocyte membrane ( 2 ). Activation of an intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
163
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(191 citation statements)
references
References 21 publications
(24 reference statements)
15
163
4
Order By: Relevance
“…12 In fact, we 52 and others 8 have recently shown that FA uptake by activated BAT can reach such extent that BAT activation lowers plasma triglyceride levels. BAT activation through cold exposure largely reduces plasma triglyceride levels in hypertriglyceridemic Apoa5 −/− mice 8 as well as in normolipidemic C57Bl/6J mice, suggesting that BAT activation is a promising target to combat hypertriglyceridemia.…”
Section: Bat Activation and Browning As A Tool To Alleviate Hypertrigmentioning
confidence: 99%
See 3 more Smart Citations
“…12 In fact, we 52 and others 8 have recently shown that FA uptake by activated BAT can reach such extent that BAT activation lowers plasma triglyceride levels. BAT activation through cold exposure largely reduces plasma triglyceride levels in hypertriglyceridemic Apoa5 −/− mice 8 as well as in normolipidemic C57Bl/6J mice, suggesting that BAT activation is a promising target to combat hypertriglyceridemia.…”
Section: Bat Activation and Browning As A Tool To Alleviate Hypertrigmentioning
confidence: 99%
“…8,51 Collectively, these data would rather suggest that BAT at least also takes up triglyceride-derived FA via selective delipidation of TRL in a similar manner as heart, skeletal muscle, and WAT. 48,49 Recently, Khedoe et al 52 injected TRL-like particles in coldexposed mice and observed a large increase in the selective Figure 1. Activated brown adipose tissue (BAT) takes up triglyceride (TG)-derived fatty acids after lipolysis.…”
Section: 49mentioning
confidence: 99%
See 2 more Smart Citations
“…This requires the action of lipoprotein lipase. This enzyme increases its activity during cold exposure, which presumably refl ects its increased synthesis within brown fat cells and secretion in the capillary lumen [124]. BAT has a considerably higher fatty acid releasing capacity than white fat [122].…”
Section: Brown Adipose Tissue Metabolism and Thermogenesismentioning
confidence: 99%